2011
DOI: 10.1186/1471-2393-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Utility of local health registers in measuring perinatal mortality: A case study in rural Indonesia

Abstract: BackgroundPerinatal mortality is an important indicator of obstetric and newborn care services. Although the vast majority of global perinatal mortality is estimated to occur in developing countries, there is a critical paucity of reliable data at the local level to inform health policy, plan health care services, and monitor their impact. This paper explores the utility of information from village health registers to measure perinatal mortality at the sub district level in a rural area of Indonesia.MethodsA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
2
17
0
1
Order By: Relevance
“…22 – 31 A case study in rural Indonesia demonstrated the usefulness of local maternal and child health registers as sources of information in measuring and reporting perinatal mortality and stillbirths, in combination with local vital registration systems. 32 Even in an urban area of a developed high-income country, such as the United States of America, the use of computer-assisted active surveillance revealed 14 new maternal deaths, resulting in an 88% increase in the ascertainment of maternal deaths. 33 Other innovative strategies employed to improve the reporting of deaths include record linkage, a retrospective survey among doctors, use of an interview census and confidential forms, specific inquiries on maternal deaths, a household census of birth and infant deaths, matching of hospital records with death certificates and a retrospective population-based survey.…”
Section: The Review Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…22 – 31 A case study in rural Indonesia demonstrated the usefulness of local maternal and child health registers as sources of information in measuring and reporting perinatal mortality and stillbirths, in combination with local vital registration systems. 32 Even in an urban area of a developed high-income country, such as the United States of America, the use of computer-assisted active surveillance revealed 14 new maternal deaths, resulting in an 88% increase in the ascertainment of maternal deaths. 33 Other innovative strategies employed to improve the reporting of deaths include record linkage, a retrospective survey among doctors, use of an interview census and confidential forms, specific inquiries on maternal deaths, a household census of birth and infant deaths, matching of hospital records with death certificates and a retrospective population-based survey.…”
Section: The Review Systemmentioning
confidence: 99%
“…This problem may have been exacerbated by a lack of awareness about the importance of accurate reporting and inconsistencies in community access to local health-care services. 32 Further health reforms and policy reviews may well be needed, at both district and state levels, if good data on infant and maternal deaths are to be collected in the long term. An external evaluation of the cost–effectiveness of the review system is still needed.…”
Section: The Review Systemmentioning
confidence: 99%
“…An estimated 3.2 million stillbirths occur worldwide each year with more than 98% of these in low to middle‐income countries (1,2). Stillbirth rates may be as high as 30–40 per 1 000 births in low‐income countries, especially areas of sub‐Saharan Africa and south Asia, while rates as low as 3–4 per 1 000 are reported in many high‐income countries (2–8). In low‐income countries, a gestational age of 28 weeks or a birthweight of 1 000g is often selected as the lower limit of viability (4).…”
Section: Introductionmentioning
confidence: 99%
“…National policies and recommendations are present in some countries; however, healthcare professionals are often unaware or uncertain about its content (Lawn et al, 2007). Moreover, the amount of research conducted in poor countries has decreased during the last few decades (Rudan et al, 2005); the picture of health is not always clear due to absence of resources and methods for reporting (Burke et al, 2011;Malqvist, 2011;Rudan et al, 2005). Thus, there is little information on which to base interventions or draw conclusions about the country's needs.…”
Section: Discussion and Implications For Global Neonatal Healthmentioning
confidence: 99%